AIDA's Strategy in Alfina's Food Jatikalang Prambon Sidoarjo via Instagram (@bociinaja.sda) - Savana, Ylin Diva; Hariyanto, Didik (Procedia of Social Sciences and Humanities, 2024)
The Instagram application is currently widely used as a marketing medium. Such as the form of implementing a new marketing strategy on Alfina's food business through its Instagram account. The purpose of this study is to find out the form of sales increase strategies in Alfina's food marketing through Instagram, by interviewing the owner, 10 Instagram followers, and several literature. Using a descriptive qualitative method using the AIDA effect hierarchy model theory. The results of the research obtained are Alfina's food marketing communication strategy in Instagram media is included in a strategy that uses the theory of the AIDA effect hierarchy model of E.St.Elmo Lewis carried out by means of digital marketing such as introducing products to target consumers, uploading posts containing information and promoting products more attractively, making a promo or discount on product purchases, and make it easier for consumers to make purchases and also provide good and fast service responses. So that it can produce a purchase action that comes from consumer interest and confidence in the product.